Hepatitis C Virus Non-structural Protein 3 (HCV NS3): A Multifunctional Antiviral Target - Raney, Kevin D.; Sharma, Suresh D.; Moustafa, Ibrahim M.; Cameron, Craig E. (The Journal of biological chemistry, 2010)
Hepatitis C virus non-structural protein 3 contains a serine protease and an RNA helicase. Protease cleaves the genome-encoded polyprotein and inactivates cellular proteins required for innate immunity. Protease has emerged as an important target for the development of antiviral therapeutics, but drug resistance has turned out to be an obstacle in the clinic. Helicase is required for both genome replication and virus assembly. Mechanistic and structural studies of helicase have hurled this enzyme into a prominent position in the field of helicase enzymology. Nevertheless, studies of helicase as an antiviral target remain in their infancy.